Execution of the National School Feeding Program during the pandemic: challenges and barriers (Research, Society and Development, 2021)
The aim of this study is to report the experience of implementing the National School Feeding Program (PNAE) in a municipality in Piaui during the COVID-19 pandemic, focusing on the challenges and obstacles associated with the program in the face of social isolation. As for the methodology applied, this is a descriptive study, of the experience report type, which discusses the implementation of the PNAE in a Department of Education of a Piauí City Hall based on the practice experienced by the nutritionist responsible for the program, in the period between April 2020 and April 2021. The information in the report was collected and/or observed after authorization from the City Hall and the Department of Education. The PNAE was put into operation through the distribution of “school lunch kits” to the families of students from the Municipal Education Network, which were basically composed of non-perishable foods that are common in the local eating habits. Food from family farming composed the kits only once during the period studied. The number of families served ranged from 838 to 1361, according to changes in the selection criteria adopted. The results of this study show the difficulties faced by the Executing Entity for the development of the PNAE during the closing of schools. The identified barriers are associated with the impossibility of meeting school feeding guidelines, such as universal service, equal access and support for sustainable development, which, mainly due to the insufficiency of available financial resources, may not have been observed during the distribution of school meals to the families of the students in the period pictured.